2002
DOI: 10.1161/hy0202.103442
|View full text |Cite
|
Sign up to set email alerts
|

Preproendothelin-1 Gene Polymorphism Is Related to a Change in Vascular Reactivity in the Human Mammary Artery In Vitro

Abstract: Abstract-A gene polymorphism of preproendothelin-1 (a G-to-T transversion that predicts a Lys/Asn change at codon 198) associated with an increased risk of hypertension has been recently described in patients carrying the T allele. No study has yet determined the impact of this polymorphism on vascular reactivity, although a functional role for endothelin-1 in the pathophysiology of hypertension has been clarified. At subthreshold concentrations, endothelin-1 and angiotensin II induce a potentiation of ␣-adren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 33 publications
3
30
0
1
Order By: Relevance
“…The same allele has been reported previously to be associated with elevated resting DBP in obese Japanese subjects, 9 elevated resting and exercise SBP in overweight whites, 10 increased BP reactivity to a video game challenge, 12 and with increased in vitro vascular reactivity. 28 Therefore, our novel discovery of a significant relationship between rs5370 and SBP responsiveness to endurance training is concordant with existing data on other hemodynamic phenotypes, ie, the T allele is associated with a less favorable hemodynamic profile. The functional significance of rs5370 is not clear at this time.…”
Section: Discussionsupporting
confidence: 83%
“…The same allele has been reported previously to be associated with elevated resting DBP in obese Japanese subjects, 9 elevated resting and exercise SBP in overweight whites, 10 increased BP reactivity to a video game challenge, 12 and with increased in vitro vascular reactivity. 28 Therefore, our novel discovery of a significant relationship between rs5370 and SBP responsiveness to endurance training is concordant with existing data on other hemodynamic phenotypes, ie, the T allele is associated with a less favorable hemodynamic profile. The functional significance of rs5370 is not clear at this time.…”
Section: Discussionsupporting
confidence: 83%
“…Its widespread potential effects include modification of risk for HTN in the overweight/obese population (41-43), BP reactivity to stressors (44)(45)(46), idiopathic pulmonary arterial Figure 4. Comparison in European descent subjects and African descent subjects of aldosterone/renin ratio was obtained on a restricted salt diet.…”
Section: Discussionmentioning
confidence: 99%
“…Of the studied polymorphisms, the rs5730 polymorphic variant was associated with blood pressure in overweight people of European 22 and Japanese descent 23 . Iglarz et al confi rmed the impact of rs5370 polymorphism on vascular reactivity 28 , while Treiber et al demonstrated that the rs5370 polymorphism infl uences blood pressure response to behavioral stress in obese subjects from lower socio-economic status 51 . Li et al identifi ed the Asn/Asn genotype of EDN1 rs5370 polymorphism as a genetic factor for delayed onset of T2DM and reduced risk of diabetic retinopathy in T2DM patients of Chinese descent.…”
Section: Discussionmentioning
confidence: 99%
“…EDN1 has been identifi ed as a strong candidate gene for cardiovascular and renal disease. Various single nucleotide polymorphisms (SNPs) in the EDN1 gene were linked to arterial hypertension 22,23 , heart failure 24 , coronary artery disease 25,26 , left ventricular hypertrophy 27 , modifi cation of vascular reactivity 28 , endothelial dysfunction 29 , progression of atherosclerosis 30 , as well as with accelerated decline in kidney function in the chronic glomerulonephritis patients 31 , and with end stage renal disease attributed to hypertension 32 . In addition, EDN1 genetic variability was related to microvascular complications of T2DM such as diabetic retinopathy 33 , and DN 34 .…”
mentioning
confidence: 99%